In-situ TEM investigation of zirconium alloy under Kr+ single-beam and Kr+-He+ dual-beam synergetic irradiation - Zhen Wang; Qing-Xue Yan; Zhong-Qiang Fang; Chen-Yang Lu (Nuclear Engineering and Technology, 2024)
The in-situ TEM irradiation experiments of zirconium alloy were conducted at 573 K, 673 K, and 773 K utilizing a 400 keV Kr + single beam and a 400 keV Kr+ and 30 keV He + dual beam. The results show that a large number of dislocation loops have been characterized in the matrix of the zirconium alloy under irradiation. With increasing the irradiation damage dose, some dislocation loops have reacted with one another to form a larger dislocation loop, which has finally formed dislocation lines or other defect structures. In zirconium alloys irradiated with Kr + single beam and Kr+ and He + dual-beam radiation, the proportion of type dislocation loops with different Burgers vectors is essentially the same at low damage doses, but the proportion of interstitial type dislocation loops with the same Burgers vectors is obviously different. The amorphization of the second phase and the dissolution of the small-sized second phase were also pointed out. With the increase in temperature, the density of the dislocation loop in zirconium alloy gradually decreases, and the size of dislocation loop first increases and then decreases. Kr+ and He + dual beam irradiation increases the size of dislocation loops but decreases their density as compared with Kr + single beam irradiation.